Mind Mapping Model in Increasing Students’ Creativity and Learning Outcomes - Kulsum, Nur Umi (Unversitas Negeri Malang, 2018)
This study was conducted in order to determine that the application of Mind Mapping learning model toward students’ creativity and student learning outcomes in economics subject. This paper applied in class X IPS 2 Brawijaya Smart School in Malang. This matters addressed to overcome the problem in the classroom related to students’ creativity and learning achievement. The study followed a classroom action research with qualitative descriptive analysis. The study was conducted in two cycles where each cycle consisted of four steps consisting of planning; Implementation, observation, and reflection. Therefore, the presence and role of researchers in the field are indispensable. The data were collected from observation sheets, documentation, field notes, test questions. Based on the research that has been conducted in Brawijaya Smart School in Malang, It can be known that the implementation of Mind Mapping learning model can improve student’s creativity on economic subjects. In addition, Mind Mapping learning also promotes better learning outcomes on economic subjects.Keywords: Mind Mapping, Creativity, Learning Outcomes